1994
DOI: 10.1111/j.1467-9280.1994.tb00503.x
|View full text |Cite
|
Sign up to set email alerts
|

What Is Average and What Is Not Average About Attractive Faces?

Abstract: We reported in this journal (Langlois & Roggman, 1990) findings showing that attractive faces are those that represent the mathematical average of faces in a population These findings were intriguing because they provided a parsimonious definition of facial attractiveness and because they supported explanations of attractiveness from the point of view of both evolutionary and cognitive-prototype theory Since our 1990 report, several alternative explanations of our findings have been offered In this article… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

11
181
4
11

Year Published

1996
1996
2015
2015

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 320 publications
(207 citation statements)
references
References 38 publications
11
181
4
11
Order By: Relevance
“…According to cognitive averaging theory, attractive faces are closer to the population average in configuration and are thus perceived as more familiar, typical, and "face-like" than faces that deviate (e.g., unattractive faces) from the average configuration of a population of faces (see Langlois & Roggman, 1990;Langlois, Roggman & Musselman, 1994;Rubenstein, Kalakanis & Langlois, 1999;Rubenstein, Langlois, & Roggman, 2002). Indeed, faces that are rated as more typical are categorized as faces more quickly than those rated as less typical by both children and adults (Johnston & Ellis, 1995) and attractiveness facilitates the sex classification of faces by children and adults (Hoss, Ramsey, Griffin, & Langlois, in press).…”
Section: Discussionmentioning
confidence: 99%
“…According to cognitive averaging theory, attractive faces are closer to the population average in configuration and are thus perceived as more familiar, typical, and "face-like" than faces that deviate (e.g., unattractive faces) from the average configuration of a population of faces (see Langlois & Roggman, 1990;Langlois, Roggman & Musselman, 1994;Rubenstein, Kalakanis & Langlois, 1999;Rubenstein, Langlois, & Roggman, 2002). Indeed, faces that are rated as more typical are categorized as faces more quickly than those rated as less typical by both children and adults (Johnston & Ellis, 1995) and attractiveness facilitates the sex classification of faces by children and adults (Hoss, Ramsey, Griffin, & Langlois, in press).…”
Section: Discussionmentioning
confidence: 99%
“…Since the majority of past research in the field has characterised the perception and effects of beauty or appearance in terms of attractiveness, we asked participants to rate faces along two dimensions: age and attractiveness, instead of fatigue (Berry 1991;Langlois et al 1994). While Nguyen et al may have predicted that perception of fatigue would be closely related to age judgments, our methodological changes provide a bridge to the literature on attractiveness, which along with age is the main dimension which people seek to alter with cosmetic surgery.…”
Section: Introductionmentioning
confidence: 99%
“…The relationship between perceived attractiveness and computationally defined facial averages has been debated vigorously in a number of recent papers (Alley & Cunningham, 1991;Langlois & Roggman, 1990;Langlois, Roggman, & Mussleman, 1994;Langlois, Roggman, Mussleman, & Acton, 1991;Pittenger, 1991). Langlois and Roggman (1990) found that composite faces, created by arithmetically averaging the images of several male or female faces, were judged to be more attractive than almost any single male or female face.…”
mentioning
confidence: 99%